How can the Dual‐atom Catalyst FeCo–NC Surpass Single‐atom Catalysts Fe–NC/Co–NC in CO2RR? – CO Intermediate Assisted Promotion via a Synergistic Effect. Issue 1 (22nd March 2022) - Cao, Shoufu; Zhou, Sainan; Chen, Hongyu; Wei, Shuxian; Liu, Siyuan; Lin, Xiaojing; Chen, Xiaodong; Wang, Zhaojie; Guo, Wenyue; Lu, Xiaoqing
Abstract : Atomically dispersed catalysts are widely adopted in CO2 reduction reaction (CO2 RR) due to maximal atomic utilization and high catalytic activity. Dual‐atom catalysts (DACs), with more dispersed active sites and distinct electronic structures compared with single‐atom catalysts (SACs), may exhibit diverse catalytic performance. Herein, the DAC FeCo–NC and SAC Fe–NC/Co–NC are employed as probes to explore DACs advantage in CO2 RR. Results show that the moderate interaction between the dual‐atom center and N coordination balances structural stability and catalytic activity. CO is the only product on Fe–NC/Co–NC, and the high limiting potentials from −1.22 to −1.67 V inhibit further reduction. FeCo–NC assisted with CO intermediate exhibits low limiting potentials of −0.64 V for both CH3 OH and CH4, comparable to those on Cu‐based catalysts. Under circumstance of applied potentials, CO2 RR on FeCo–NC has greater advantages in yielding CH3 OH and CH4 than that on Fe–NC/Co–NC, and hydrogen evolution reaction is severely inhibited. The intrinsic essence is that dual‐atom center can provide large spin‐polarization and multi‐electron transfer capability, rendering CO intermediates as effective electronic and geometric modifiers in CO2 RR. This work highlights FeCo–NC as a high‐performance CO2 RR catalyst toward deep‐reduction C1 products and elucidates CO intermediate assisted promotion mechanism via a dual‐atom synergistic effect. Abstract : By virtue of CO intermediate assisted promotion mechanism via the dual‐atom synergetic effect, FeCo–NC dual‐atom catalyst exhibits higher CO2 RR activity toward CH3 OH and CH4 than Fe–NC/Co–NC single‐atom catalysts. Fe, Co dual atoms working in synergy facilitate the CO intermediate as an effective electronic and geometric modifier to boost CO2 RR and inhibit HER.